RW-BP100-4D, a Promising Antimicrobial Candidate With Broad-Spectrum Bactericidal Activity - Tong, Xingqi; Li, Jun; Wei, Ruicheng; Gong, Lan; Ji, Xing; He, Tao; Wang, Ran (Frontiers in Microbiology, 2022)
With the rapid emergence and dissemination of antimicrobial resistance (AMR) genes in bacteria from animal, animal-derived food and human clinic, it is of great significance to develop new approaches to combat the multidrug-resistant bacteria. This study presented a short linear antimicrobial peptide RW-BP100-4D, which was derived from RW-BP100 (RRLFRRILRWL-NH2) by transforming the N-terminal 4th amino acid from L- to D-enantiomer. This modification remarkably reduced the peptide cytotoxicity to mammalian cells as indicated by hemolytic and cytotoxicity assays. Meanwhile, the antimicrobial activity of RW-BP100-4D was improved against a more variety of Gram-positive and Gram-negative bacteria (sensitive and resistant) as well as fungi. Also, RW-BP100-4D showed strong anti-biofilm activity in a concentration-dependent manner, including inhibition of the biofilm-formation and dispersion of the mature biofilms of Staphylococcus aureus. RW-BP100-4D could be efficiently uptaken by MAC-T cells to eliminate the intracellular S. aureus ATCC29213 and Salmonella enterica ATCC13076. Moreover, RW-BP100-4D was highly effective in food disinfection of multiple bacterial contamination (including S. aureus, Listeria monocytogenesis, Escherichia coli O157: H7, Campylobacter jejuni, S. enterica and Shewanella putrefaction, 3.61±0.063 log reduction) on chicken meat, and could kill 99.99% of the MRSA strain in the mouse skin infection model. In summary, RW-BP100-4D is a promising antimicrobial candidate for application on food disinfection and local infection treatment, and further study is needed to improve the serum stability of RW-BP100-4D for in vivo antimicrobial applications.